Why Confronting the Internet's Dark Side? - Cohen-Almagor, Raphael (Philosophia, 2017)
Raphael Cohen-Almagor, the author of Confronting the Internet's Dark Side, explains his motivation for exploring the dangerous side of the world wide web. This new book is the first comprehensive book on social responsibility on the Internet.